Log in to add a comment

## Answers

x=k/y^2

substituting y=3 and x=4

we get

4=k/3^2

4=k/9

multiplying both sides by 9

4*9=k

k=36

finding x when y=6

so substituting y=6 and k=36 in x=k/y^2

x=36/6^2

x=36/36

x=1

hence the value of x when y=6 is

__1__

Log in to add a comment

x=k/y^2

substituting y=3 and x=4

we get

4=k/3^2

4=k/9

multiplying both sides by 9

4*9=k

k=36

finding x when y=6

so substituting y=6 and k=36 in x=k/y^2

x=36/6^2

x=36/36

x=1

hence the value of x when y=6 is